Challenges in the extrapolation from DD to DT plasmas: experimental analysis and theory based predictions for JET-DT. (27th October 2016) - Garcia, J; Challis, C; Gallart, D; Garzotti, L; Görler, T; King, D; Mantsinen, M
Abstract: A strong modelling program has been started in support of the future JET-DT campaign with the aim of guiding experiments in deuterium (D) towards maximizing fusion energy production in Deuterium–Tritium (DT). Some of the key elements have been identified by using several of the most updated and sophisticated models for predicting heat and particle transport, pedestal pressure and heating sources in an integrated modelling framework. For the high beta and low gas operational regime, the density plays a critical role and a trend towards higher fusion power is obtained at lower densities. Additionally, turbulence stabilization by E × B flow shear is shown to generate an isotope effect leading to higher confinement for DT than DD and therefore plasmas with high torque are suitable for maximizing fusion performance. Future JET campaigns will benefit from this modelling activity by defining clear priorities on their scientific program.